Analisis Beban Kerja dengan Pendekatan Cardiovascular (CVL) dan Subjective Workload Assesment Technique (SWAT) : Studi Kasus Pengemudi Go-Jek - Muhammad Rifqi Hari Nugroho; Akmal Suryadi (Universitas Trunojoyo Madura, 2023)
Currently the mobility of the population is getting higher and higher which causes congestion and the emergence of demands to move from one place to another by using an online motorcycle taxi. Being an online motorcycle taxi driver is inseparable from physical and mental activities such as driving, controlling vehicles, carrying goods ,waiting for orders, interacting with customers, finding destination addresses, operating online motorcycle taxi applications and others. This makes the workload of online motorcycle taxi riders both physically and mentally even greater. this study aims to determine the physical and mental workload on the Go-Jek driver in the village of tongue Kulon. This research uses a quantitative approach. The population of this study is Go-Jek drivers who are active as a whole in the village of tongue Kulon which amounted to 35 people and a sample of 26 respondents. The results of this study found that the physical workload using the percentage of Cardiovascular Load (CVL) showed that Go-Jek drivers have a physical workload with an average of %CVL of 31%. Then the results of the SWAT method for Go-Jek drivers obtained values in the Effort dimension of 23.69%, then for Time of 64.43%, and for Stress of 11.89%. Then the most influential is the Load Time with an average load value of 64.43%. This means that Gojek drivers significantly feel the burden of time is more dominant in affecting their work.